Factors affecting nutritional status of children below 24 months in Pekan district, Pahang, Malaysia - Masroor , Nagis; Ab Rahman, Jamalludin; Tin, Myo Han; Khattak, Muhammad Muzaffar Ali Khan; Aye , Aye (Nutrition Society of Malaysia, 2014)
Introduction: This study aimed to assess the nutritional status of children below 24 months in the district of Pekan, Pahang, and identify the contributing factors. Methods: Using a cross-sectional methodology, a total of 910 children was selected by random sampling from four public health clinics. Anthropometric measurements were taken and weight-for-age, height-for-age, and weight-forheight were calculated in Z scores. Immediate caregivers of children were interviewed by using a pretested validated questionnaire to assess their socioeconomic,demographic, educational and occupational status. Results: Of the 910 children who participated in the study, the majority were Malay (70.1%),while the remaining comprised indigenous or Orang-Asli (OA) children. Prevalence of wasting, stunting and underweight were 28.7 %, 15.6 % and 19.0% respectively. There were more underweight males than females. Wasting was most common among children aged below 6 months. Stunting was more prevalent in children between 12 to 24 months. Obesity was seen in 7.3% of the sample. Maternal education, employment and socio-economic status had a significant influence on wasting and underweight. Children were vulnerable to stunting as age advanced, whereas prevalence of wasting tended to decrease. Conclusion: Malnutrition exists in significant proportions among children below 24 months in the Pekan district. This study identified low birth weight along with age, race, gender, large family size and socio-economic status as important risk factors of malnutrition.